The Influence Of Product Quality, Price, And Promotion On Customer Buying Interest In Store Thrifting Uncle P Outfit Kediri - Safana, Yunia Dwi; Samari, Samari (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : The purpose of this study was to determine the influence of product quality, price, and promotion on customer buying interest in thrifting Store Uncle P Outfit Kediri Design/Methode/Approach : This research uses a quantitative approach, and the method used is the causality method. The population in this study were customers of Uncle P Outfit Kediri. The sampling technique is based on the multivariate method, where the number of variables (both independent and dependent) is multiplied by 10. So with 4 variables, the number of samples in this study was 40 respondents. Data collection was carried out by distributing questionnaires. Data analysis techniques for testing hypotheses using the SPSS version 25 program. Research Finding : The results showed that the product quality variable had a positive and significant effect on customer buying interest at the Store Thrifting Uncle P Outfit Kediri, the price and promotion variables had a positive and insignificant effect on customer buying interest at the Store Thrifting Uncle P Outfit Kediri. Theoretical contribution/Originality : The results of this study indicate that product quality needs to be a concern for the Thrifting Store Uncle P Outfit Kediri, because this aims to increase customer buying interest to be even better in order to achieve goals. Practitionel/Policy implication : This research provides practical implications for Store Thrifting Uncle P Outfit Kediri in increasing customer buying interest. Research limitation : This research is limited to other samples. It is hoped that future research can use a larger sample, and can increase the number of respondents who fill out the questionnaire.